POSITION OF THE QUR’AN MEMORY AS A PRICE PAYMENT MEDIA IN BUY AND SELL - Muhamad Izazi Nurjaman; Sofian Al-Hakim; Didah Durrotun Naafisah; Doli Witro (UIN Siber Syekh Nurjati Cirebon, 2023)
AbstractThis research intends to describe a theme regarding the view of sharia economic law on the media of payment for buying and selling prices using the memorization of the Al-Qur’an. Using descriptive research (case study) through the method of collecting information in the form of interviews and documentation. This research found the fact that the view of sharia economic law equates or qiyas between the media of paying prices using the memorization of the Al-Qur’an with the dowry in the marriage contract. Giving a dowry is allowed to memorize the Al-Qur’an with the provision that it is mandatory to teach the Qur’an, as well as the practice of buying and selling. So that there is a wage in the form of benefits. Meanwhile, benefits include assets. So between the dowry and the price of both is something that has qimah madiyyah (property value). Indirectly, the buyer pays the price using the ujrah of the teaching. So that the harmony of buying and selling has been fulfilled properly and non-material benefits will lead to a business concept full of blessings.Keywords: Buy and Sell; Price; Wedding; Dowry; Memorizing Al-Quran.